A 3-year retrospective analysis of microbial species and key biomarkers associated with wound infections in Shantou Hospital, China - Khan, Sabir; Hou, Bing; Khan, Muhammad Nadeem; Shafiq, Muhammad; Cai, Lin; Fang, Wenjie; Wang, Qian; Bilal, Hazrat; Zeng, Yuebin (Frontiers in Cellular and Infection Microbiology, 2025)
A biomarker is an important indicator of a normal physiological or pathological process, or a pharmacological response to a therapeutic intervention. This retrospective study aimed to measure blood biomarkers in wound patients, identify the microorganisms responsible for wound infections and determine their drug susceptibility patterns at a tertiary care hospital in China. The study was conducted between 2022 and 2024, including 279 patients. A total of 33 microbial species were isolated using culture techniques, identified, and analyzed for their antibiotic susceptibility. The organisms were predominantly gram-positive (50.8%), with Staphylococcus aureus (80.2%) being the most prevalent species. Among the gram-negative bacteria (41.2%), Pseudomonas aeruginosa (22.6%) was the most predominant species. Biomarkers such as white blood cells, neutrophils, lymphocytes, and erythrocyte sedimentation rate (ESR) values were higher than normal in most of microbial species associated with wound infections. The WBC value in gram-positive infections and the neutrophil and ESR values in fungal infections were statistically significantly higher than the normal range (p = 0.0002, p = 0.002, and p = 0.003, respectively). Albumin levels were high value in P. aeruginosa and K. pneumoniae (0.48 and 0.56 respectively), while lymphocytes levels were the lowest value (-0.62) in S. aureus. Resistance to at least one antibiotic was identified in 82.4% of the isolates. The prevalence of multidrug-resistant microbes in different wound infections is a significant concern in China. A health awareness campaign, coupled with improved hygiene measures, should be implemented to prevent the spread of microorganisms responsible for wound infections within the community.